Influence of stimulus colour and form over the identification time - Gutauskas, A.; Bertulis, A. (Elektronika ir Elektrotechnika, 1998)
The colour is the main factor determining the stimulus form under the same subjective brightness. The corresponding exposure ratio for different colours conditions the equal parameters of the form identification processes. Results are discussed on the ground of the spatial frequency filtering.